Motivasi Disiplin Dan Kepuasan Kerja Pengaruhnya Terhadap Kinerja Karyawan - Wachid Hasyim (Universitas Persada Indonesia YAI, 2021)
This study aims to determine and analyze the effect of motivation on employee performance,this study also aims to determine and analyze the effect of discipline on employeeperformance, and aims to determine and analyze the effect of job satisfaction on employeeperformance. The type of research used is quantitative. With the population are employees ofPT. Cakrawala Teknik Mandiri Indonesia with a total of 42 respondents. Data collectionincludes observation, distributing questionnaires and literature study. The analytical methodused is the classical assumption test, validity test, reliability test, hypothesis testing andmultiple linear regression test. The results of the research conducted concluded that partiallythe motivational variable had an effect on employee performance, the discipline variable hadan effect on employee performance and the job satisfaction variable had an effect onemployee performance. This is evidenced by the t-count value which is greater than the ttablevalue with a significant value below the value α.